Esterification of levulinic acid to ethyl levulinate over bimodal micro-mesoporous H/BEA zeolite derivatives - Patil, C. R.; Niphadkar, P. S.; Bokade, Vijay V.; Joshi, P. N. (Catalysis Communications, 2014)
A series of bimodal micro-mesoporous H/BEA zeolite derivatives were prepared by the post-synthesis modification of H/BEA zeolite by NaOH (0.05 M-1.2 M) treatment Samples were characterized by powder XRD, low temperature nitrogen adsorption/desorption, temperature programmed desorption of ammonia and ICP. The mesopore formation was found to play a crucial role in liquid phase esterification of levulinic acid with ethanol. The enhanced catalytic activity of a bimodal micro-mesoporous H/BEA zeolite derivative (H/BEA(0.10)) prepared by treatment with 0.1M NaOH can be mainly attributed to the high mesoporosity coupled with better preserved crystallinity and acidic properties. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Esterification; ethyl levulinate; H/BEA zeolite; Mesoporosity; Post-synthesis modification

Tandem synthesis of glycidol via transesterification of glycerol with DMC over Ba-mixed metal oxide catalysts - Kondawar, S. E.; Patil, C. R.; Rode, C. V. (ACS Sustainable Chemistry & Engineering, 2017)
Glycerol carbonate (GC) and glycidol (GD) are commercial products possible from glycerol transformation, which has become a subject of great importance. Among several basic catalysts screened in this work, BaO showed the highest glycerol conversion of 71% with almost complete selectivity to GC. A tandem synthesis of GD with a selectivity as high as 80% with 98% glycerol conversion could be achieved with mixed oxides of Ba and lanthanides (La and Ce) prepared by the coprecipitation method. Although BaO alone showed the highest basicity as measured by CO2 TPD, tuning of basicity by incorporation of CeO2 resulted in the formation of GD. Incorporation of Ba into the ceria matrix induced oxygen vacancies in the cerium oxide material. The presence of u"/v" doublets at 888.7 and 903.2 eV, respectively, in XPS of the Ba-Ce sample also confirmed the oxygen vacancies in the lattice. In this tandem approach to GD, the subsequent decarboxylation of initially formed GC was due to the presence of a CeO2 lattice with defects, which is known to be the best for CO2 adsorption. Increase in both catalyst loading and temperature showed a dramatic enhancement in GD selectivity. A plausible reaction pathway for the transesterification of glycerol with DMC to give GC followed by its decarboxylation to GD is also proposed based on the structural characterization and activity studies.